2012
DOI: 10.1364/oe.20.005586
|View full text |Cite
|
Sign up to set email alerts
|

Pulse propagation through a slab with time-periodic dielectric function ε(t)

Abstract: We describe pulse propagation through a slab with periodic dielectric function ε(t), thus extending our previous investigation for monochromatic incidence [Phys. Rev. A 79, 053821 (2009)]. Based on the concepts of phase and group delays, we prove that, for an incident quasi-monochromatic pulse, the transmitted pulse can be expressed as a superposition of partial pulses that are exact replicas of the incident pulse and that exit the slab with a time delay. These partial pulses have harmonic carrier frequencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The above expressions (31) and (32) show that due to the nonlinear nature of the system, the waves acquire frequency shifts (the first two terms), which can be adjusted to the chirped driving frequencies continuously (see the last term), yielding control of the wave amplitudes.…”
Section: Weakly Nonlinear Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above expressions (31) and (32) show that due to the nonlinear nature of the system, the waves acquire frequency shifts (the first two terms), which can be adjusted to the chirped driving frequencies continuously (see the last term), yielding control of the wave amplitudes.…”
Section: Weakly Nonlinear Equationsmentioning
confidence: 99%
“…For example, the optical properties of photonic time crystals with a refractive index varying periodically in time have been investigated in Refs. [29][30][31][32][33][34][35][36]. The optical properties of the structures possessing periodicity both in space and time have been studied in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez et al investigated the interaction of light with a dielectric slab with a time-periodic dielectric function (t). More specifically, the transmission and reflection coefficients were derived [40], and the pulse case was discussed in detail [41]. Recently, Daniel et al found that…”
Section: Previous Studies In the Microwave Regionmentioning
confidence: 99%
“…However, recent experimental advances in dynamic optical materials, especially in epsilon-near-zero (ENZ) materials ( 13 , 14 ), hold the promise of having PTCs at optical frequencies very soon: Recent experiments showed large (on the order of ∼1), femtosecond-scale variations in the refractive index ( 15 , 16 ). These and later experiments of time refraction ( 17 – 19 ) herald the possibility to experiment with PTCs in the near future ( 6 , 20 ).…”
mentioning
confidence: 99%